1)      Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{2}{x}+\frac{4}{x}=1+\frac{1}{x}

 

\displaystyle b)\quad 1+\frac{3}{d}=\frac{5}{d}+2

 

\displaystyle c)\quad 4-\frac{6}{v}=\frac{1}{v}+4

 

\displaystyle d)\quad \frac{4}{x}+2=3-\frac{6}{x}

 

\displaystyle e)\quad \frac{2}{p}-\frac{7}{2p}+1=-\frac{9}{2p}

\displaystyle f)\quad \frac{2}{4y}+3=3+\frac{4}{8y}

 

\displaystyle g)\quad \frac{5}{3a}+\frac{6}{a}-\frac{11}{6a}=2-\frac{13}{6a}

 

\displaystyle h)\quad 2-\frac{1}{2x}-\frac{6}{5x}-\frac{3}{10x}=0

 

\displaystyle i)\quad \frac{7}{8u}-\frac{5}{12u}=\frac{5}{6u}-\frac{3}{4}

 

\displaystyle j)\quad 1-\frac{2}{9b}+\frac{4}{3b}=\frac{1}{6b}-\frac{5}{12}


 

2)      Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{2}{u}-1=\frac{1}{u}-\frac{1}{2}

 

\displaystyle b)\quad \frac{2}{r}+\frac{3}{r}-1=\frac{3}{r}-3

 

\displaystyle c)\quad \frac{2}{u}+\frac{3}{2u}=1+\frac{1}{u}

\displaystyle d)\quad 1-\frac{2}{v}=1\frac{5}{8}+\frac{1}{2v}

 

\displaystyle e)\quad \frac{0,5}{z}+\frac{1,5}{2z}-1=1,5

 

\displaystyle f)\quad \frac{1}{2s}+1=-\left( \frac{1}{2s}+1 \right)


 

3)      Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{x+6}{x-2}=5

 

\displaystyle b)\quad \frac{7-3a}{a+6}=2

 

\displaystyle c)\quad \frac{4t-7}{t+3}=4

 

\displaystyle d)\quad -3=\frac{2v-9}{3-4v}

 

\displaystyle e)\quad \frac{4z+3}{3\left( z+2 \right)}=3

 

\displaystyle f)\quad \frac{5-3x}{2\left( 6x-1 \right)}=2

\displaystyle g)\quad \frac{10x-3}{5\left( 3-5x \right)}=-1

 

\displaystyle h)\quad \frac{m+5}{4m+2}=-\frac{1}{2}

 

\displaystyle i)\quad \frac{1-2p}{6p-9}=\frac{1}{3}

 

\displaystyle j)\quad \frac{4r-7}{8r-2}=-\frac{5}{2}

 

\displaystyle k)\quad \frac{x+1}{x-2}=\frac{5}{2}

 

\displaystyle l)\quad \frac{7-10y}{5y+3}=\frac{3}{5}


 

4)      Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{4}{t-10}=\frac{6}{t-6}

 

\displaystyle b)\quad \frac{2}{u+10}=\frac{8}{5-3u}

 

\displaystyle c)\quad \frac{5}{3x+13}=\frac{1}{1-x}

 

\displaystyle d)\quad \frac{4}{6-5r}=\frac{2}{2r+3}

 

\displaystyle e)\quad \frac{9}{5-p}=\frac{3}{p+11}

\displaystyle f)\quad \frac{4}{3a-4}=\frac{8}{3a+1}

 

\displaystyle g)\quad \frac{1}{-2-x}=\frac{3}{x+10}

 

\displaystyle h)\quad \frac{9}{5z+7}=\frac{6}{9-z}

 

\displaystyle i)\quad \frac{7}{4-c}=\frac{14}{10-c}

 

\displaystyle j)\quad \frac{6}{21-y}=\frac{3}{y-6}


 

5)      Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{u+2}{u+3}+\frac{u+3}{u+4}=2

 

\displaystyle b)\quad \frac{n+1}{n-1}-\frac{n-1}{n+1}=0

 

\displaystyle c)\quad z+\frac{z+1}{z-2}=\frac{{{\left( z-1 \right)}^{2}}}{z-2}

 

\displaystyle d)\quad \frac{4}{m-6}=\frac{5}{m}

 

\displaystyle e)\quad \frac{s-1}{s-2}=2

\displaystyle f)\quad \frac{r+7}{r-5}+\frac{r+5}{r-7}=2

 

\displaystyle g)\quad \frac{x-2}{x}+\frac{x}{x-1}=2

 

\displaystyle h)\quad \frac{5}{2\left( z+3 \right)}-1=\frac{1}{2}-\frac{3}{z+3}

 

\displaystyle i)\quad \frac{3}{n-3}+n=\frac{{{\left( n-1 \right)}^{2}}}{n-3}


 

6)      Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{x+3}{x-5}+\frac{x-10}{x-8}=2

 

\displaystyle b)\quad \frac{a-1}{a+7}+\frac{a+6}{a+4}=2

 

\displaystyle c)\quad 3=\frac{2s+1}{s+2}+\frac{s-7}{s-1}

 

\displaystyle d)\quad \frac{5v-4}{v-1}-\frac{v+6}{v+2}=4

 

\displaystyle e)\quad \frac{7k+4}{k+1}+\frac{2k+9}{k-3}=9

\displaystyle f)\quad \frac{9d+7}{d+1}-\frac{4d-1}{2d+1}=7

 

\displaystyle g)\quad \frac{4x+1}{x-1}+\frac{3x+2}{3x+7}=5

 

\displaystyle h)\quad \frac{9t+3}{4t-2}-\frac{t+12}{4t+3}=2

 

\displaystyle i)\quad \frac{8p+3}{3p-2}-\frac{4p-1}{6p+11}=2

 

\displaystyle j)\quad \frac{3x-4}{x+4}+\frac{6x-4}{3x-7}=5


 

7)      Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{1}{s-1}+\frac{1}{s}=\frac{2}{s+1}

 

\displaystyle b)\quad \frac{1}{s-1}-\frac{2}{s}=\frac{3}{1-s}

\displaystyle c)\quad \frac{s}{2s-3}-\frac{1}{2}=\frac{1}{s-3}

 

\displaystyle d)\quad \frac{s+1}{s}-\frac{s}{s-8}=\frac{11}{8-s}


 

8)      Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{r-2}{5}-\frac{2r-9}{10}=\frac{5}{r+3}

 

\displaystyle b)\quad \frac{4x+5}{8}-\frac{x+1}{2}=\frac{1}{x+13}

 

\displaystyle c)\quad \frac{u+3}{3}-\frac{8}{u+11}=\frac{3u+1}{9}

 

\displaystyle d)\quad \frac{3z-2}{6}-\frac{z-2}{2}=\frac{4}{z+3}

\displaystyle e)\quad \frac{v+2}{2}-\frac{5v+6}{10}=\frac{4}{v+9}

 

\displaystyle f)\quad \frac{2x+7}{6}-\frac{x+4}{3}=\frac{2}{x-6}

 

\displaystyle g)\quad \frac{s+1}{4}-\frac{3s-1}{12}=\frac{4}{9-s}

 

\displaystyle h)\quad \frac{7a-4}{14}-\frac{3}{3a+8}=\frac{a-1}{2}


 

9)      Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{x+7}{x-2}-\frac{x-2}{x+2}=-\frac{3}{{{x}^{2}}-4}

 

\displaystyle b)\quad \frac{b-2}{b-1}+\frac{4-b}{b+1}=\frac{6}{{{b}^{2}}-1}

\displaystyle c)\quad \frac{t-4}{t+3}-\frac{10}{{{t}^{2}}-9}=\frac{t-6}{t-3}

 

\displaystyle d)\quad \frac{m+1}{2m-3}-\frac{7}{4{{m}^{2}}-9}=-\frac{4-m}{2m+3}